2011
DOI: 10.1002/ar.21247
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Estrogen Receptors in Two Hippocampal Regions During the Estrous Cycle of the Rat

Abstract: In the hippocampus, estrogens increase dendritic arborization, longterm potentiation, neuroprotection, and participate in many functions related with learning, memory, and affective behaviors. The presence of both estrogen receptors alpha (ERa) and beta (ERb) isoforms has been described in the hippocampus where they play different physiological roles. The aim of this study was to investigate, by using both techniques immunohistochemistry and Western Blot, the expression pattern of ERa and ERb in the hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…51,55 Regarding the vmPFC, both ERα and ERβ have been detected in the rat IL and prelimbic cortex. 56, 57, 58 A summary of relative receptor distribution within the fear extinction network is illustrated in Figure 3.…”
Section: Estradiol Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…51,55 Regarding the vmPFC, both ERα and ERβ have been detected in the rat IL and prelimbic cortex. 56, 57, 58 A summary of relative receptor distribution within the fear extinction network is illustrated in Figure 3.…”
Section: Estradiol Receptorsmentioning
confidence: 99%
“…E2 receptors exhibit sensitivity to estradiol fluctuations, with expression and cellular localization varying across the phases of the rat estrous cycle in the hippocampus 57 and hypothalamus. 60 In the cornu ammonis 1 (CA1) subregion of the hippocampus, for instance, ERα expression correlates with serum estradiol levels and shows greatest expression during estrus, whereas ERβ is upregulated during both estrus and metestrus phases.…”
Section: Estradiol Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific ER expression in brain regions important for the STFP therefore likely dictate whether 17␤-E2 enhances social learning or not. As ER expression changes over the estrous cycle (Mendoza-Garcés et al, 2011), this may explain when and how strongly 17␤-E2 affects social learning in females and why social learning is affected by the phase of the estrous cycle . Further research is necessary to explore possible additive effects of ER activation on the STFP.…”
Section: Overall Drug Effectsmentioning
confidence: 99%
“…Of note, we have previously demonstrated that FGR affects the newborn rat hippocampus in a region-specific manner, FGR decreased neuronal numbers and subregional volumes in the CA1 and DG volumes in FGR males but not in the CA3 region [Fung et al 2012]. Region-specific changes in ERα expression in the hippocampus are not only limited to FGR, but also occur in kainate-induced hippocampal injury [Vanoye-Carlo et al 2009] and varies throughout the estrous cycle [Mendoza-Garces et al 2011]. Interestingly, the observed region-specific reduction in apparent ERα staining levels using immunohistochemistry was observed in the absence of measurable changes in whole hippocampal ERα levels by Western blotting.…”
Section: Discussionmentioning
confidence: 98%